Incidence and spatiotemporal distribution of plasmodium knowlesi infection in Pahang from 2011 To 2022 - Bakar, Abdul Muntaqim Abu (2023)
Introduction: Plasmodium knowlesi malaria poses a significant public health challenge in Pahang and Malaysia, as it can result in severe and fatal malaria cases in humans. Moreover, this disease threatens efforts towards malaria elimination. An analysis of the incidence and spatiotemporal patterns of P. knowlesi malaria is necessary to gather crucial information for identifying high-risk areas, making informed decisions, and allocating resources effectively for malaria control and prevention. Objective: The study aims to evaluate the incidence rate and spatiotemporal distribution of P. knowlesi infection in Pahang from 2011 to 2022. Methodology: The study was a cross-sectional study conducted from January 2023 to June 2023, using a retrospective secondary data review of reported P. knowlesi cases that met the predefined inclusion criteria from the e-Vekpro system in Pahang. A descriptive analysis and mapping of the incidence rate were conducted. Density and cluster analysis were performed using Kernel Density Estimation (KDE) and Nearest Neighbour Index (NNI), respectively. While Global Moran’s I and LISA statistics for autocorrelation at the subdistrict level. Spatial analysis was done using R software version 4.2.3. Result: Of 967 confirmed P. knowlesi malaria registered in Pahang from 2011 to 2022, the majority were male (83.7%). The mean age was 36.9 (SD = 15.83), and the Malay predominants (58.3%). The average 12 years incidence rate of P. knowlesi in Pahang was 0.053 cases per 1,000 population and exhibited an upward and downward trend, with peaks in 2013, 2018, and 2021. The Lipis district has a high density of P. knowlesi malaria cases, together with the neighbouring districts of Raub and Jerantut. P. knowlesi cases exhibited clustering patterns (NNI <1) except for 2011, 2015, 2016, and 2019. The results of the autocorrelation analysis indicated the presence of positive spatial correlation during the years 2012 and 2013 and identified specific hotspot areas located in the subdistricts of Tembeling, Cheka, Kechau, Telang, and Gua. Conclusion: The incidence rate of P. knowlesi malaria in Pahang has shown fluctuations over the course of 12 years, with peaks in incidence observed in 2013, 2018, and 2021, which were characterised by higher density, clustering, and correlation in rural subdistricts of Pahang. Public health authorities should prioritise targeted prevention in the identified high-risk areas, including enhancing surveillance and monitoring for populations at risk, strengthening vector control measures, and organising community education initiatives.